DIALEKTIKA RELASIONAL PADA MAHASISWA DALAM PEMBELAJARAN SECARA DARING DI MASA PANDEMI COVID-19 - Sunani, Eneng (STAI Darul Qalam Tangerang, 2022)
This study aims to find out how the relational dialectic occurs to students in online learning during the Covid-19 pandemic. This study uses a qualitative approach that emphasizes meaning rather than generalizations, and the sampling technique used is purposive sampling according to the research objectives. The results of the study show that online learning during the COVID-19 pandemic has changed student relationships dialectically which can be described in three relational situations, namely: student-to-student relationships, student-teacher relationships, and student-families relationships. All elements of dialectics occur in the three relations, namely the element of totality where there is an interdependent relationship between them, the element of contradiction which is marked by the attraction of the relationship, the element of movement where over time the relationship undergoes a process of change, and the element of praxis which is indicated by the existence of decisions. decisions and the consequences of those choices in the relationship. The most prominent element of contradiction occurs in the relationship between students and lecturers where there are different desires so that there is an attraction in their relationship